THE CORRELATION OF GANDHI’S WRITING SPIRIT TOWARD INDONESIAN’S WRITING CULTURE - Nugroho, Adi (LPPM STKIP PGRI Bandar Lampung, 2020)
The impact of globalization has caused so many changes in our social life. One of the impacts is technology that we must be familiar with. Moreover, the influence of technology has encompassed in almost all aspects. As the technology improves, recently comes up the term to manifest the era of technology that we know as revolutionary of 4.0. The revolution 4.0 has brought a challenge to all countries to have capability to compete not only within their own country but also with the whole world. Therefore, every country needs to produce appropriate human resource who is capable with it otherwise they will be left behind. That is why, it is hoped that each country need to be well prepared in facing this technology era or the revolution 4.0. One of the countries that have made its own preparation is Indonesia. Indonesia is one of the biggest countries in the south East Asia that has 17.508 islands with the total of the wide is about 1.9 million km2 and achieves as the fourth most populous in the world. This huge amount of Indonesia make the government realize that Indonesia needs to well prepare. One of the apects that is concerned by the govenment of Indonesia is education. Since education becomes the door of the successful of youth generation future, it is a must that the government has to take a step. That is why, the growing of level research project in Indonesia is quite significance. Thus, the government asks univeristy as the spearhead of education to design a curriculum relateted to revolution 4.0. Therefore, writing becomes one of the main concerned in realizing this project. By producing a lot of of writing text, a country will gain much knowledge from the result of the text itself ad so do the people of the country. Unfortunatly, it is quite difficult to plant the spirit of writing in Indonesian. Since we know that Mahatma Gandhi is a famous and good writer from India who is able to drive out the colonisation of Britain from India, not by violence but by his idealism and thought that set forth in his writing and speech imitates Mahatma Gandhi’s spirit of writing in his era might be increased the Indonesian’s spirit in producing a text. Moreover, in this technological era the writing activity can be done much easier and fun through some devices and web writing that can be access in internet freely and easily. As a conclusion, Gandhi’s spirit in writing and the ease of access through the writing field may overcome the Indonesians writing spirit and also make Indonesia able to face the challenge in the revolution 4.0.